2006
DOI: 10.1002/cbdv.200690117
|View full text |Cite
|
Sign up to set email alerts
|

Two New Taxanes from the Needles and Branches Bark of Taxus cuspidata

Abstract: Two new taxanes were isolated from the MeOH extract of the needles and branches bark of the Japanese yew, Taxus cuspidata. The structures were established as (2alpha,5alpha,7beta,9alpha,10beta,13alpha)-5,10,13,20-tetraacetoxytax-11-ene-2,7,9-triol (1) and (2alpha,5alpha,9alpha,10beta)-2,9,10-triacetoxy-5-[(beta-D-glucopyranosyl)oxy]-3,11-cyclotax-11-en-13-one (2) on the basis of in-depth 1D- and 2D-NMR analyses. Compound 2 is the first example of a transannular taxane glycoside isolated from a natural source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…Compound 2 was isolated as a gummy solid, [α] D 22 : + 73 (c 0.05, MeOH), and its molecular formula was established as C 26 H 36 O 10 (HR-FAB-MS: m/z = 551.2263 [M + K] + , Δ = + 0.4 mmu). The 1 Hand 13 C-NMR spectral data (l "Table 2) almost coincided with the known taxane 5α,10β,13α,20-tetraacetoxytax-11-ene-2α,7β,9αtriol, which was isolated by us from the bark of T. cuspidata[13], except for the chemical shift values of the 20 position (Δδ H = − 0.59 and − 0.49 ppm, Δδ C = − 1.8 ppm) and one missing acetyl group. This information together with analysis of 2D NMR spectral data revealed that the structure of 2 was 5α,10β,13α-triacetoxytax-11-ene-2α,7β,9α,20-tetraol.The following equipment and materials were used: optical rotation, Jasco DIP-370; NMR, Bruker Avance-500; HR-FAB-MS, Vacuum Generators ZAB-HS; preparative HPLC, Waters Delta Prep 3000, UV 2487, Partisil 10 ODS-2 MAG-20 (9.4 × 250 mm); TLC, EM Science silica gel 60 F 254 ; column chromatography, EM Science silica gel 60 (230-400 mesh).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Compound 2 was isolated as a gummy solid, [α] D 22 : + 73 (c 0.05, MeOH), and its molecular formula was established as C 26 H 36 O 10 (HR-FAB-MS: m/z = 551.2263 [M + K] + , Δ = + 0.4 mmu). The 1 Hand 13 C-NMR spectral data (l "Table 2) almost coincided with the known taxane 5α,10β,13α,20-tetraacetoxytax-11-ene-2α,7β,9αtriol, which was isolated by us from the bark of T. cuspidata[13], except for the chemical shift values of the 20 position (Δδ H = − 0.59 and − 0.49 ppm, Δδ C = − 1.8 ppm) and one missing acetyl group. This information together with analysis of 2D NMR spectral data revealed that the structure of 2 was 5α,10β,13α-triacetoxytax-11-ene-2α,7β,9α,20-tetraol.The following equipment and materials were used: optical rotation, Jasco DIP-370; NMR, Bruker Avance-500; HR-FAB-MS, Vacuum Generators ZAB-HS; preparative HPLC, Waters Delta Prep 3000, UV 2487, Partisil 10 ODS-2 MAG-20 (9.4 × 250 mm); TLC, EM Science silica gel 60 F 254 ; column chromatography, EM Science silica gel 60 (230-400 mesh).…”
supporting
confidence: 56%
“…T. cuspidata is one of the most extensively investigated yews, and more than 120 taxanes have been isolated from it [1][2][3][4][5][6]. As a continuation of our research on plants from the Taxus genus, we reinvestigated the leaves of T. cuspidata collected at Sendai, Japan [7][8][9][10][11][12][13][14][15], and isolated three new taxanes (l " Fig. 1 [10,11,16]).…”
mentioning
confidence: 99%
“…Therefore the signal at H 1.84 (1H, d, J ¼ 2:4 Hz) was attributed to H-1. Continuing this spin system, the signals at H 5.02 (1H, dd, J ¼ 9:5, 5.0 Hz), 2.75 (1H, dd, J ¼ 9: 5 Note tions with C-3 and C-20. 7) The chemical shift of H-5 implied that a free hydroxy group was connected to C-5.…”
mentioning
confidence: 98%
“…Irradiation of the corresponding 13-oxotax-11-enes led to the bonding between C(3) and C(11); however, only a mixture of isomers was obtained ((Z)-and (E)-configured side-chains) [92], and the 3,11-bridge rendered the structure less flexible. Taxinine K (27) and taxinine L (28) are the first two 3,11-cyclotaxanes from T. cuspidata [40], while taxuspine H (30) is the sole 3,11-cyclotaxane with an alkaloid side chain at C(5) [36], and 34 is the first 3,11-cyclotaxane with a glycoside at C(5) [38] (see Fig. 3).…”
mentioning
confidence: 99%